An Analysis of the Recording, Reporting, and Use of School Attendance Data in Australia - Matthew Oliver White (Karolinum Press, 2022)
Despite the growing body of literature on school attendance, there is relatively little known about the different approaches that are used to define, record, and report school attendance across countries. This paper seeks to fill this literature gap by providing a policy analysis of how attendance and absenteeism are defined, measured and reported in Australia. This paper explores how school attendance is conceptualised in Australia, with a specific focus on New South Wales where the author resides. The analysis examines what indicators of absence are recorded and how schools along with education authorities make use of this data. The national setting of goals to improve the educational outcomes of all Australian young people has been a driver behind the collection and public reporting of attendance data. This policy analysis highlights the multilateral achievement of the Commonwealth, state and territory governments in Australia to nationally align the collecting and reporting of school attendance data. This has elevated the importance of attendance beyond an administrative task to its current position as a key performance indicator of school effectiveness.